Financial Innovations Designed to Mitigate Climate Risks - Hurduzeu, Gheorghe; Popescu, Maria Floriana (International Journal of Economic Practices and Theories, 2015)
This research paper aims to build a mechanism suitable for hedging the climatic risks by using financial innovations. The research starts from the premise that the climatic changes during the past years have had a significant impact on the level of agricultural production, cost, prices, and income stability both at the level of agricultural exploitations but also the economic indices at macroeconomic level. Then, following a risk management evaluation, we propose the establishment of a portfolio of indices on the evolution of the meteorological events (rain and temperature). Based on these indices there can be drawn the standardized elements of a contract for derivatives used as alternative mechanisms for the transfer of the agro-climatic risks. The understanding of the weather risks and the exposure to such risks has undergone a growth in complexity, aiming for a proactive risk management strategy for all the players in the agricultural field affected by climate change.